The Antecedents of Non-Unqualified Opinions of Local Governments Financial Statements: A Study on Counties and Cities in East Java Province - Ningsih, Sri (Asian Journal of Accounting Research, 2016)
Local Government in Indonesia annually publishes Local Government Financial Statements (LGFS) for helping their stakeholders in making decisions. Audit Opinion of the LGFS for counties and cities in East Java Province during the last 8 years (2006-2013) showed a quite astonishing result. From all of 301 financial statements, only 45 LGFS (14.95%) obtained Unqualified Opinion, other financial statements (256 or 85.05%) received Non-Unqualified Opinion. This study aims to analyze the accounts and problems in the accounts which cause LGFS obtain Non-Unqualified Opinion. Using content analysis with NVIVO10 applications, this study analyzed 256 audit opinions of the LGFS of counties and cities in East Java during 2006-2013 that obtained Non-Unqualified Opinion to identify the accounts and problems in the accounts which cause LGFS obtain Non-Unqualified Opinion. The results showed that the most frequent accounts as an exception in the audit opinion are the accounts on Budget Realization Report (BR) with the frequency of occurrence as much as 6628 times. The Balance Sheet (BS) accounts was at the second place with the total frequency of occurrence 4206 times. And last, there was a Cash Flow Statement (CF) account with the frequency of occurrence as much as 693 times. In BR, the most frequent account which appears as an exception is spending account (as much as 4198 times), while the assets are the most frequent accounts as an exception in the Balance Sheet (as much as 4206 times). The problem with the accounts that often appear as an exception was mainly due to the weakness of the Internal Control System (ICS), followed by non-compliance with the provisions of law and the last problem is in-economies, inefficiency and ineffectiveness.